Examining tourists’ intentions to participate in tea tourism. An emerging market context - Dutta, Enakshi; Soodan, Vishal; Jassal, Tajinder; Jain, Anurag (Turyzm/Tourism, 2023)
Tea tourism, a growing niche segment within the broader realm of culinary and cultural tourism, has gained prominence as an emerging market opportunity. This study investigates the factors influencing tourists’ intentions towards tea tourism. The research uses the stimulus-organism-response (S-O-R) framework, incorporating variables like destination credibility, authenticity, destination image, attitude and an intention to visit tea tourism destinations. Data from 392 domestic tourists were analyzed using structural equation modelling (CB-SEM). Key findings underscore the importance of factors such as destination image, tea-related knowledge and prior tea tourism experiences in shaping tourists’ intentions. This research not only contributes to the emerging tea tourism market but also offers valuable insights for destination marketers, policymakers and tea industry stakeholders. Understanding these influencing factors can help tailor marketing strategies and offers to make tea tourism destinations more appealing, thus supporting sustainable growth in this burgeoning industry. Ultimately, this study sheds light on the preferences of tourists seeking immersive tea experiences and guides efforts to develop and promote tea-related tourism experiences effectively.